2020
DOI: 10.1001/jamanetworkopen.2020.11079
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inferior Vena Cava Filter Placement With Rates of Pulmonary Embolism in Patients With Cancer and Acute Lower Extremity Deep Venous Thrombosis

Abstract: IMPORTANCE Venous thromboembolism is the second overall leading cause of death for patients with cancer, and there is an approximately 2-fold increase in fatal pulmonary embolism (PE) in patients with cancer. Inferior vena cava (IVC) filters are designed to prevent PE, but defining the appropriate use of IVC filters in patients with cancer remains a substantial unmet clinical need. OBJECTIVE To evaluate the association of IVC filters with the development of PE in patients with cancer and deep venous thrombosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…It has been reported that the life quality score of patients with PTS is comparable to that of patients with severe chronic diseases such as diabetes and congestive heart failure [ 5 ]. Anticoagulant therapy has always been the standard scheme recommended by some guidelines for the treatment of acute LEDVT [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the life quality score of patients with PTS is comparable to that of patients with severe chronic diseases such as diabetes and congestive heart failure [ 5 ]. Anticoagulant therapy has always been the standard scheme recommended by some guidelines for the treatment of acute LEDVT [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A population-based study of cancer patients with acute lower extremity DVT demonstrated an improvement in PE-free survival on long-term follow-up in patients with IVCF insertion (for any indication) compared to those without (HR, 0.69; 95% CI, 0.64-0.75). 106 The proportion of new DVT among patients who received IVCF was slightly lower than in patients who did not receive IVCF (18.7% versus 22.1%; respectively, P < 0.001). A prospective cohort study of cancer patients with acute PE or lower extremity DVT used propensity score matching to compare 30-day outcomes between patients with IVCF placement because of a significant bleeding risk versus patients without IVCF placement.…”
Section: Anticoagulant Therapymentioning
confidence: 83%
“…were comparable between DOACs and LMWH groups [15]. In another meta-analysis comparing [17]. In another cohort study, a significant lower risk of PE-related mortality (0.8% vs 4.0%; p = 0.04) were observed in patients receiving IVCF due to contraindication against anticoagulation compared with those who did not, without significant between-group difference regarding the major bleeding rate (6.1% vs 5.7%; p = 0.85).…”
Section: Treatment Of Established Cancer-associated Vte Within 6 Monthsmentioning
confidence: 91%
“…With respect to IVCF, a cohort study demonstrated that among 33, 740 cancer patients with acute lower extremity DVT and bleeding risk factors who underwent IVCF placement, 4492 patients (5.1%) developed a new PE after the initial DVT diagnosis. A significant improvement was observed in PE-free survival for patients who received IVCF compared with those who did not [ 17 ]. In another cohort study, a significant lower risk of PE-related mortality (0.8% vs 4.0%; p = 0.04) were observed in patients receiving IVCF due to contraindication against anticoagulation compared with those who did not, without significant between-group difference regarding the major bleeding rate (6.1% vs 5.7%; p = 0.85).…”
Section: Treatment Of Established Cancer-associated Vte Within 6 Montmentioning
confidence: 99%